A new technique to prepare hard fruits and seeds for anatomical studies1. (12th October 2015) - Benedict, John C.
Abstract : Premise of the study: A novel preparation technique was developed to examine fruits and seeds of plants with exceptionally hard or brittle tissues that are very difficult to prepare using standard histological techniques. Methods and Results: The method introduced here was modified from a technique employed on fossil material and has been adapted for use on fruits and seeds of extant plants. A variety of fruits and seeds have been prepared with great success, and the technique will be useful for any excessively hard fruits or seeds that are not able to be prepared using traditional embedding or sectioning methods. Conclusions: When compared to existing techniques for obtaining anatomical features of fruits and seeds, the protocol described here has the potential to create high‐quality thin sections of materials that are not able to be sectioned using traditional histological techniques, which can be produced quickly and without the need for harmful chemicals.